2017
DOI: 10.1016/j.ebiom.2017.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Memory B Cells are Major Targets for Effective Immunotherapy in Relapsing Multiple Sclerosis

Abstract: Although multiple sclerosis (MS) is considered to be a CD4, Th17-mediated autoimmune disease, supportive evidence is perhaps circumstantial, often based on animal studies, and is questioned by the perceived failure of CD4-depleting antibodies to control relapsing MS. Therefore, it was interestingly to find that current MS-treatments, believed to act via T cell inhibition, including: beta-interferons, glatiramer acetate, cytostatic agents, dimethyl fumarate, fingolimod, cladribine, daclizumab, rituximab/ocreliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
259
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 238 publications
(277 citation statements)
references
References 97 publications
15
259
1
2
Order By: Relevance
“…Disease-driving lymphocytes, including B-cells, are believed to migrate to the CSF and CNS from peripheral stores during phases of MS disease activity (8,11,12). Due to their immunological properties and functionality, SM B-cells are generally believed to be highly relevant to the immune pathology of MS (35). Indeed, when persistent PB SM cells were clonally related to second time-point CSF B-cells, these T2-CSF cells were nearly always SM and PC.…”
Section: Discussionmentioning
confidence: 99%
“…Disease-driving lymphocytes, including B-cells, are believed to migrate to the CSF and CNS from peripheral stores during phases of MS disease activity (8,11,12). Due to their immunological properties and functionality, SM B-cells are generally believed to be highly relevant to the immune pathology of MS (35). Indeed, when persistent PB SM cells were clonally related to second time-point CSF B-cells, these T2-CSF cells were nearly always SM and PC.…”
Section: Discussionmentioning
confidence: 99%
“…We selected Cladribine for the following reasons: (1) class I evidence of efficacy of the active compound in people with relapsing MS10, 15, 22; (2) selective lymphocyte mechanism of action not requiring cell‐proliferation and notably B cell targeting potential that appears to be associated with effective control of active MS23, 24; (3) CNS penetration for peripheral and CNS immune cell inactivation and modulation16, 23; (4) safety comparable or better than similarly effective, current treatments12; (5) known relative safety in people with advanced MS15; (6) induction therapy potential requiring only short courses of treatment10 with rapid elimination from the body potentially allowing additional use of neuroprotection and symptomatic treatments without complications due to drug‐drug interactions23; and importantly, (7) convenience for the patient with easy and rapid administration during brief hospital visits to our day case unit, and few monitoring needs compared to some of the current DMT. This will limit travel requirements for someone restricted to a wheelchair.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased frequency of B cells following treatment with DMF has been reported by several investigators (Chaves et al, ; Claes et al, ; Diebold et al, ; Fleischer et al, ). It has been shown that DMF preferentially targets the B memory cells, which are worthy targets for MS immunotherapy (Baker et al, ; Smith et al, ). Although DMF reduced the incidence of CD27 + IgD memory B cells it increased the incidence of CD27 ‐ IgD + naıve B cells (Smith et al, ).…”
Section: Mechanism(s) Of Dmf Actionmentioning
confidence: 99%